Métodos de otimização combinatória aplicados ao problema de projeto de redes FTTx - Tormann, Suzianne Miranda (2023)
Due to technological advances, quality internet access is becoming increasingly indispensable, just like other urban infrastructure networks such as water and electricity supply. This new and growing demand gives rise to the passive optical network planning problem (FTTx) that aims to minimize the cost of deployment and attenuation of the signal received by the customer. This work proposes two mixed integer programming models to minimize the deployment costs of a fiber optic network, considering the selection/location of balanced and unbalanced splitters and the available power budget. Computational results demonstrate that the proposed models adequately represent reality and, when solved with commercial solvers, provide practically implementable solutions for instances with up to 128 customers.